An insight into attitude about usage of ICT by teachers in school for hearing impaired - Prabhu, Vaishali; Srividya, A.; T., Suresh; Babu, Praveena (International Journal Of Community Medicine And Public Health, 2023)
Background: Information and Communication Technology (ICT) in education is the mode of education that depends on digital medium of information transfer for delivery of course content and related learning experiences. Its focus is on utilization of different technologies in order to support, enhance, and optimise the delivery of information. ICT can be used in many ways to help both the students and the teachers gain knowledge on a particular topic/subject. The present study was inclined to look into the attitude of teacher for the hearing impaired towards usage of ICT in classrooms. Methods: Questionnaire which consists of attitude of teachers towards ICT. The questionnaire used for this study was adopted and modified from the original questionnaire designed by Gulbahar and Guven (2008), Ghavifekr and Athirah (2015) that is considered suitable for this research. Descriptive statistics was carried out for analyzing the data in SPSS version 20.0. Results: For all the questions framed to elicit positive opinions, the median values were either 4 i.e. agree is the common response of all the judges. For questions framed to elicit the common response is either disagree or strongly disagree. The responses of the judges suggest that they consider ICT to be helpful for teaching-learning of hearing impaired children. Conclusions: The study was able to demonstrate that ICT tools have gained popularity among the teachers of hearing impaired included in the study.